Pharmaceuticals in the environment - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology., 2015)
Medicines play an important role in the treatment and prevention of disease in humans and animals, but residues from these medicines can be released into the environment through a number of routes during their manufacture, use and disposal. It is only recently that the potential environmental impacts of this exposure to pharmaceuticals are being considered. The book explores where pharmaceutical residues can be found, e.g. in surface waters, drinking water, sediments and the marine environment; the sources of these residues, from manufacture through to disposal of unused medicines; how these residues break down; and how this all impacts on wildlife and human health. In reviewing the current position and examining further possible impacts, this book is an important reference for researchers working in the pharmaceutical industry, as well as for environmentalists, policy makers and students on pharmacy and environmental science courses wanting to better understand the impacts of pharmaceuticals on the environment.